2011
DOI: 10.1007/s00122-011-1707-4
|View full text |Cite
|
Sign up to set email alerts
|

A QTL for rice grain yield in aerobic environments with large effects in three genetic backgrounds

Abstract: A large-effect QTL associated with grain yield in aerobic environments was identified in three genetic backgrounds, Apo/(2)*Swarna, Apo/(2)*IR72, and Vandana/(2)*IR72, using bulk-segregant analysis (BSA). Apo and Vandana are drought-tolerant aerobic-adapted varieties, while Swarna and IR72 are important lowland rice varieties grown on millions of hectares in Asia but perform poorly in aerobic conditions. Two closely linked rice microsatellite (RM) markers, RM510 and RM19367, located on chromosome 6, were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 22 publications
5
33
1
Order By: Relevance
“…Similar results were observed by Lilley and Fukai (1994b). Yield components such as spiklelet fertility and the number of panicles per hill were also low in our study as have been observed in other studies (Garrity and O'Toole, 1994;Bernier et al, 2007;Kumar et al, 2008;Venuprasad et al, 2009Venuprasad et al, , 2012Verulkar et al, 2010). These observations suggest that the imposition of regulated water stress during vegetative growth may lead to yield advantage even for the drought-susceptible rice varieties.…”
Section: Positive Yield Response and Recovery In Vegetative Stagesupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results were observed by Lilley and Fukai (1994b). Yield components such as spiklelet fertility and the number of panicles per hill were also low in our study as have been observed in other studies (Garrity and O'Toole, 1994;Bernier et al, 2007;Kumar et al, 2008;Venuprasad et al, 2009Venuprasad et al, , 2012Verulkar et al, 2010). These observations suggest that the imposition of regulated water stress during vegetative growth may lead to yield advantage even for the drought-susceptible rice varieties.…”
Section: Positive Yield Response and Recovery In Vegetative Stagesupporting
confidence: 91%
“…There was 12.5% reduction in yield with increased stress level in vegetative stress in 2012 growing season. This was an exceptional behaviour in this experiment, which may have occurred because of highly drought susceptible nature of IR72 (Venuprasad et al, 2012) and significant negative correlation between chaffy grains per hill and terminal SWP. As a lowland reference variety, IR72 showed an average yield reduction of 67-80% (Belder et al, 2004;Atlin et al, 2006;Serraj et al, 2011;Venuprasad et al, 2011) and failed to perform in aerobic condition (Zhao et al, 2010), due to severely reduced biomass and harvest index.…”
Section: Positive Yield Response and Recovery In Vegetative Stagementioning
confidence: 76%
“…This QTL has also been reported in CT9993-5-10-1-M/IR62266-42-6-2 and Apo/IR64 populations Venuprasad et al, 2012a).…”
Section: Qtl For Yield and Yield Related-traits Under Droughtsupporting
confidence: 77%
“…BSA was successfully used for the first time to identify such large-effect QTLs for grain yield under reproductive-stage drought (Venuprasad et al , 2009). qDTY 6.1 , another large-effect QTL for grain yield under favourable aerobic and irrigated lowland conditions, was identified in this population (Venuprasad et al , 2012 a ). This QTL explained an R 2 of up to 66% and 39%, respectively, under upland and lowland non-stress conditions.…”
Section: Resultsmentioning
confidence: 92%